Bureaucratic Reform, Digital Transformation, and Public Service Quality in Indonesia: An Analysis of Achievements and Implementation Gaps in 2023 - Septiawan Ardiputra (Journal of Communication and Social Sciences, 2024)
This study aims to analyze the achievements and implementation gaps in bureaucratic reform, digital transformation, and public service quality in Indonesia in 2023. A qualitative approach using Qualitative Document Analysis (QDA) was employed to examine four official documents: the 2020-2024 Bureaucratic Reform Road Map, the 2023 Performance Report of the Ministry of Administrative and Bureaucratic Reform, the 2023 Electronic-Based Government System (SPBE) Evaluation Report, and the 2023 Executive Summary of the Public Service Compliance Assessment. The analysis combined deductive and inductive coding, cross-document comparison, and source triangulation. The findings indicate that bureaucratic reform and digital transformation have made progress at the aggregate level, but these advances have not been fully accompanied by equally mature implementation capacities. At the local government level, the SPBE Service Domain reached 3.38, while the Governance and Management Domains reached only 2.14 and 1.54, respectively. Meanwhile, although 70.70% of public service entities were classified in the green zone, performance variations across service providers remained evident. Cross-document analysis identified three forms of implementation gaps: a gap between policy orientation and implementation capacity, an imbalance between digital service maturity and SPBE management capacity, and variations in public service quality across service providers. This study develops the analytical concept of service-management imbalance to explain that progress in digital services must be accompanied by stronger governance and management capacity so that bureaucratic reform can produce public services that are consistent, sustainable, and outcome-oriented.